1987
DOI: 10.25249/0375-7536.19879299
|View full text |Cite
|
Sign up to set email alerts
|

Cretaceous Anoxic Events in the South Atlantic

Abstract: To charac terize the anoxi c event s in Cretaceous series in th e South Atl anti c, detail ed reinvestigations of biostratlgraph y, organic geochemist ry, and Iithology were necessary. More than 2,000 samples from different'Dâfâí' sltes were analyzed (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 1 publication
0
30
0
Order By: Relevance
“…This period of the basin's history is dominated by the deposition of the region's highest quality source rocks, the Barremian and lower Aptian black shales, which were penetrated and documented during Deep Sea Drilling Project (DSDP) 361 (Herbin et al, 1987). This sequence is overlain by more than 5500 m (18,045 ft) of postrift sediments that are dominantly of a shale or claystone lithology.…”
Section: A C K N O W L E D G E M E N T Smentioning
confidence: 98%
See 2 more Smart Citations
“…This period of the basin's history is dominated by the deposition of the region's highest quality source rocks, the Barremian and lower Aptian black shales, which were penetrated and documented during Deep Sea Drilling Project (DSDP) 361 (Herbin et al, 1987). This sequence is overlain by more than 5500 m (18,045 ft) of postrift sediments that are dominantly of a shale or claystone lithology.…”
Section: A C K N O W L E D G E M E N T Smentioning
confidence: 98%
“…As discussed in the section on geological setting and hydrocarbon system, the best developed source rock intervals in the study area are the oil-prone Barremian interval (Herbin et al, 1987) and several postulated lower Aptian black shales (Figures 1, 2) (Jungslager, 1999). The principal control on source rock maturation is the presence of overburden.…”
Section: Implications Of Margin Evolution On Hydrocarbon Prospectivitymentioning
confidence: 98%
See 1 more Smart Citation
“…The highest quality source rocks discovered in the basin are oil-prone lacustrine source rocks of Hauterivian age within graben structures, and wet-gas and oil-prone source rocks of Barremian to Aptian age. Oil-prone Aptian source rocks were intersected by the DSDP361 borehole (Herbin et al, 1987) and a number of petroleum exploration wells have shown evidence for good quality source rocks within this interval. The Barremian to Lower Aptian marine source interval appears to be regionally developed within the basin.…”
Section: Geological and Tectonic Settingmentioning
confidence: 99%
“…The lower Aptian TOC-rich Fischschiefer of northern Germany is a likely equivalent of OAE la [Gaida et al, 1981]. TOC contents are high throughout the Aptian interval of DSDP Site 361 in the Cape Basin, South Atlantic, but reach a peak of 25% in the Chiastozygus litterarius nannofossil Zone [Proto Decima et al [1978]; Herbin et al [1986Herbin et al [ , 1987. Poor nannofossil preservation does not allow subzonal subdivision of this section.…”
mentioning
confidence: 95%